Income Generation Capacity of Rural Women through Selected Entrepreneurial Activities (A Case Study of Nainital District) - Bhatt, Vipul; Sharma, Prafula (Journal of Commerce and Trade, 2017)
The poor rural women need more to be self-reliant. Economically productive activities thus can significant improve the women’s role in household and social decision making. Moreover, she can earn for her, maintain the earnings and can use this for herself and the children. Because, women’s earning has a positive correlation with health, nutritional levels and education of children in the family. All that required is to motivate poor rural women to participate in economically productive activities needed for their self-development and stability. Apart from agriculture, women must utilize her capacities through entrepreneurial activities to support their family income for further development. The study was conducted in Haldwani, Ramnagar, Nainital and Lalkhan Tehsils of Nainital District in Uttarakhand state. Rural women engaged in Shawl weaving, Carpet and mat making, Handicraft and embroidery work and Pine-wood work were taken as sample for this study which amounts to a total random sample of 60 female respondents. The income of the respondents increased significantly after taking up the selected entrepreneurial activities. The rural women utilized the income to fulfill the family requirements, for savings and on education of children. Further women reported changes in food, clothing and education of children. It can be said that income generating activities is a powerful tool for women to fight against object poverty and to become self-reliant and independent. Classification-JEL: E 24, E 25, I 10, I 20, J 11, J 16.